Patient-specific 3D cryo(bio)printing of a glenoid labrum scaffold for fibrocartilaginous tissue engineering - da Silva, Francklin Trindade; de Souza, Caio Moreira; Stocco, Thiago Domingues (Frontiers in Bioengineering and Biotechnology, 2026)
The glenoid labrum is a fibrocartilaginous structure essential for shoulder stability, yet its regeneration remains an unmet clinical challenge. Current surgical approaches restore initial joint stability but frequently fail to reestablish native biomechanics, leading to recurrence and early degenerative changes. In this study, we investigated the feasibility of fabricating a patient-specific, anatomically scaled glenoid labrum scaffold using digital modeling based on magnetic resonance imaging and 3D cryo(bio)printing of a gelatin methacryloyl (GelMA) hydrogel. Printing was performed in a temperature-controlled platform (22.5 °C, 15 °C, and −20 °C) to evaluate the influence of thermal conditions on structural fidelity and biological performance. Quantitative analyses showed that cryogenic deposition markedly improved printing precision, reducing filament spreading and enhancing geometric accuracy in both sharp-angle and grid-pattern evaluations. Biological assays indicated high viability of human mesenchymal stem cells under all temperature conditions, validating the cytocompatibility of the methodology. Morphological assessment by structured-light 3D scanning demonstrated that bioprinted patient-specific scaffold at −20 °C achieved the highest correspondence to the digital reference model. Overall, the integration of anatomical modeling with cryo(bio)printing proved to be an effective approach for producing anatomically faithful, patient-tailored scaffolds. This study presents the first demonstration of human glenoid labrum bioprinting and establishes a foundation for future translational research in fibrocartilaginous tissue regeneration.